Das Erbe der "Helden" Grabkult der Konso und kulturverwandter Ethnien in Süd-Äthiopien - Poissonnier, Nicole (Universitätsverlag Göttingen, 2009)
The work offers for the first time a comprehensive study of the anthropomorphic wooden sculptures of the Konso (waakaa) with a detailed description of the figures, their production, their symbolism, the way they are erected and associated rituals. Based on an inventory, the figures are divided into three different categories: the waakaa as a group of figures forming a memorial to a man who killed an enemy or a defensible animal, as a memorial to people who excelled in other ways, and as a grave marker for anyone who was married and had children. The study places the waakaa comparatively in the overall regional and historical context of stelae and other monuments in Ethiopia, many of which are monuments to deceased "hero killers". The waakaa of the Konso are therefore considered in the focus of the very widespread "killing practice" in earlier years. The examination of the preparations, regulations and rituals to be followed in connection with the killing makes it clear that this is a liminal rite through which a man changes to a new social status. A second focus is the connection of the waakaa with the funeral ceremonies on the occasion of which they are erected, which are particularly elaborate for "heroic slayers". In many cases, the erection of the monument is made dependent on the existence of a descendant. The size and elaborateness of the monument can in turn be used to infer the numerical size or economic position of the descendants. In this way, the kinship group can demonstrate its own strength through the elaborateness of the festivals and monuments. The number of monuments accumulated over the years thus becomes a visible symbol of the group's strength and fortitude. The analysis of these two aspects leads to the connection, already considered by previous researchers, between the act of killing by the man and his ability to beget new life. This connection is seen in terms of the concept, widespread in southern Ethiopia, of a circulating vitality that can be enriched in this way.